Real Estate Regulations in Accra: Some Macroeconomic Consequences? - Buckley, Robert M. (2012)
Ghana has been one of the most rapidly growing economies in sub-Saharan Africa. This growth has been aided by Ghana's improving policy environment. In light of this, the paper addresses the question of why, given its higher level of per capita income and relatively strong growth, the housing conditions of the poor in Accra are considerably worse than those in a number of other African cities with lower incomes. There are not many data available to answer this question, so the method is indirect and takes two approaches. First, a variant of the monocentric city model is used to calculate Accra's housing supply elasticity relative to those of other similarly sized African cities. The model suggests that housing supply responsiveness is considerably lower in Accra, a result consistent with the observed higher housing costs. Secondly, a number of traditional housing demand and reduced-form equations are estimated for Accra and the other cities. This allows the formation of a quantitative judgment about Accra's housing supply elasticity. Taken together, the two approaches indicate that lower-income families in Accra have such poor housing conditions because the market is extremely unresponsive to demand. The welfare costs of current housing and land policies are considerable. The results suggest that making Accra's real estate market more responsive would go a long way towards improving the effectiveness of the broader policy environment. It would also no doubt improve the housing conditions of the poor and help to reduce the city's expanding footprint.